Plantações de eucalipto influenciam na temperatura de superfície? - RAPHAEL CARDOSO DA SILVA (2024)
Considering the hypothesis that planted forests are advancing over areas of native vegetation and negatively affecting surrounding watercourses, this study aimed to analyze the 20-year history of planted forest areas and the impacts generated on the soil surface. Comparisons were made between pasture and forestry areas to identify the environmental and thermal advantages associated with forestry. The analyses were conducted using geoprocessing tools such as QGIS and Google Earth Engine, along with statistical methods, including Mann-Kendall and Pettitt tests, to detect trends and significant changes in temperature and land use and occupation time series. The results indicate a substantial reduction in pasture areas, from 71.04% in 2002 to 49.90% in 2022, while forestry areas increased from 3.54% to 21.97% in the same period. The conversion of pastureland to forestry leads to the mitigation of heat extremes, presenting milder temperatures over the years. These findings demonstrate that planted forests offer thermal advantages, contributing to local microclimate regulation through increased shading and evapotranspiration.